Analisis Faktor-Faktor Yang Mempengaruhi Sisa Hasil Usaha (Shu) Koperasi Unit Desa (Kud) Rejasa Di Desa Rejasa Kecamatan Penebel Kabupaten Tabanan - Rastana, I Dewa Gede; Guna, I Nyoman Ariana; Rusdianta, I Gede Made; Sarjana, I Wayan Mula (Universitas Tabanan, 2024)
Cooperatives are growing and expanding throughout Indonesia, serving as economic organizations aimed at advocating for the economic interests of their members and the wider community, especially in areas with weaker economies. The purpose of this research is to determine the partial effects of the number of members, amount of capital, and amount of loans provided to the community, and to understand the simultaneous effects of these variables on the net income of KUD Rejasa in the Penebel District, Tabanan Regency. The research findings indicate that the number of members (X1) has a positive and significant influence on the net income of KUD Rejasa, where t-value > t-table, i.e., 7.887 > 1.796. The amount of capital (X2) also has a positive and significant impact on the net income of KUD Rejasa, with t-value > t-table, i.e., 3.082 > 1.796. Similarly, the amount of loans (X3) has a positive and significant influence on the net income of KUD Rejasa, where t-value > t-table, i.e., 4.196 > 1.796. The number of members, amount of capital, and amount of loans collectively have a significant simultaneous impact on the net income of KUD Rejasa, with F-value > F-table, i.e., 332.782 > 3.59. Therefore, the variables of the number of members, amount of capital, and amount of loans simultaneously have a positive and significant effect on the net income of KUD Rejasa in the Penebel District, Tabanan Regency.